2022
DOI: 10.25259/ijpp_353_2020
|View full text |Cite
|
Sign up to set email alerts
|

Post graduate training in medical colleges of India: Resident Physicians’ perspective

Abstract: Objectives: Specialty training is one of the most crucial phases in the life of a doctor. The period involves intensive training to develop appropriate knowledge, psychomotor skills, and attitude related to the area of specialization. The students may struggle over issues during training which may prevent them from giving their best performance. The present study was aimed to assess perception of quality of academic facilities and training provided to postgraduate trainees in medical colleges and institutes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…95.6% of Indian residents meet their nancial obligations through stipends obtained during postgraduation, and 72% have adequate exposure to medical cases. 18 A study done in Lahore and Karachi also shed some light on the migration of trained doctors abroad, contributing to shortages in medical specialties. 8,13 It is also stated that various reasons, from nancial constraints to the country's current law and order situation, contribute to this brain drain.…”
Section: Discussionmentioning
confidence: 99%
“…95.6% of Indian residents meet their nancial obligations through stipends obtained during postgraduation, and 72% have adequate exposure to medical cases. 18 A study done in Lahore and Karachi also shed some light on the migration of trained doctors abroad, contributing to shortages in medical specialties. 8,13 It is also stated that various reasons, from nancial constraints to the country's current law and order situation, contribute to this brain drain.…”
Section: Discussionmentioning
confidence: 99%
“…The same problems that plague undergraduate medical education also affect postgraduate medical education in India. In a recent survey of residents in India, more than half of respondents reported that there was insufficient access to online journals, regular continuing medical education, and other resources ( 11 ). Although journal clubs exist in many residency programs, they are often infrequent because of, among other challenges, the lack of implementation guidelines.…”
mentioning
confidence: 99%